2007
DOI: 10.1002/ijc.22728
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns, the Alternate Healthy Eating Index and plasma sex hormone concentrations in postmenopausal women

Abstract: To evaluate the association between overall diet and sex hormones concentrations, we collected blood from 578 postmenopausal women ages 43 and 69 years in 1989 or 1990. Food intake was measured in 1990 via a food frequency questionnaire. We calculated the Alternate Healthy Eating Index (AHEI), and dietary patterns were identified by factor analysis. The cross-sectional association between diet and estrogens, sex hormone binding globulin (SHBG) were evaluated with linear regression and adjusted for energy and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 32 publications
0
33
1
Order By: Relevance
“…Adjusting for BMI also attenuated the associations between dietary factors and circulating steroid hormone concentrations observed by another study (Fung et al, 2007).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Adjusting for BMI also attenuated the associations between dietary factors and circulating steroid hormone concentrations observed by another study (Fung et al, 2007).…”
Section: Introductionmentioning
confidence: 76%
“…In the Nurses' Health Study (Fung et al, 2007), total estrogen and free estradiol concentrations were significantly higher among women in the highest category for consumption of the Western dietary pattern that comprised of high intakes of red and processed meats. However, this association disappeared after adjustment for BMI.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Many studies investigated the role of dietary components such as fat, protein and fiber, on serum estrogen levels, but most suffered from methodological faults, small sample size and lacked controls. The Nurses' Health Study found associations between different dietary patterns and serum estrogen levels in postmenopausal women, but the associations were lost after adjusting for BMI (Fung, Hu, Barbieri, Willett, & Hankinson, 2007). The effect of animal products and their nutrient components on circulating estrogens levels in postmenopausal women was investigated in the large Melbourne Collaborative Study (Brinkman et al, 2010).…”
Section: Physiological Influence Of Various Exogenous Sources Of Estrmentioning
confidence: 99%